Optimal Allocation of Capacitor Bank for Loss Minimization and Voltage Improvement Using Analytical Method - KC, Avinash Khatri; Regmi, Tika Ram (SCITECH Nepal, 2019)
An electric distribution system plays an important role in achieving satisfactory power supply. The quality of power is measured by voltage stability and profile of voltage. The voltage profile is affected by the losses in distribution system. As the load is mostly inductive on the distribution system and requires large reactive power, most of the power quality problems can be resolved with requisite control of reactive power. Capacitors are often installed in distribution system for reactive power compensation. This paper presents two stage procedures to identify the location and size of capacitor bank. In the first stage, the load flow is carried out to find the losses of the system using sweep algorithm. In the next stage, different size of capacitors are initialized and placed in each possible candidate bus and again load flow for the system is carried out. The objective function of the cost incorporating capacitor cost and loss cost is formulated constrained with voltage limits. The capacitor with the minimum cost is selected as the optimized solution. The proposed procedure is applied to different standard test systems as 12-bus radial distribution systems. In addition, the proposed procedure is applied on a real distribution system, a section of Sallaghari Feeder of Thimi substation. The voltage drops and power loss before and after installing the capacitor were compared for the system under test in this work. The result showed better voltage profiles and power losses of the distribution system can be improved by using the proposed method and it can be a benefit to the distribution networks.